PENGARUH PERPUTARAN MODAL KERJA DAN PERPUTARAN PERSEDIAAN TERHADAP RETURN ON ASSETS (ROA) PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dini Susmiandini; Siti Khodijah (The Asia Pacific Journal Of Management Studies, 2016)
Profitability  ratio  is  the  ratio  to  measure  financial  performance.  One indicator  of  the  profitability  ratio  that  I  use  is  Return  On  Assets  (ROA).  Return  On Assets  (ROA)  is  a  measure of the  effectiveness  of  management  in generating profits by managing its total assets. While the factors that support success to get the Return On  Assets  (ROA)  is  the  working  capital  turnover  and  inventory  turnover.  This research was conducted in order to determine the effect of working capital turnover and  inventory  turnover on  Return  On  Assets  (ROA)  in  the pharmaceutical  company listed on the Indonesia Stock Exchange 2010-2015 period. The data used is secondary data with the method of documentation in the form of  annual  financial  statements.  The  population  in  this  study  amounted  to  10 pharmaceutical companies and samples taken using purposive sampling is that there are  6  companies  sampled.  Analysis  technique  used  is  linear  regression,  Classical Assumption Test and Testing Hypotheses with use SPSS 20. Based on the test results F is known that the significance value less than 0.05 is  equal  to  0.000  which  showed  that  simultaneous  rotation  of  working  capital  and inventory  turnover  have  a  significant  effect  on  Return  On  Assets  (ROA).  And  based on t test results showed that the partial rotation of working capital significance effect on Return On Assets (ROA) with significantly smaller than 0.05 is 0.000. Based on t test  also  showed  that the  partial  inventory  turnover  have  a  significant  effect  on Return On Assets (ROA) with significantly smaller than 0.05 is equal to 0.000.